Cover Feature: Solid‐State Structure of Tris‐Cyclopentadienide Uranium(III) and Plutonium(III) (Chem. Eur. J. 12/2018). Issue 12 (8th January 2018) - Apostolidis, Christos; Dutkiewicz, Michał S.; Kovács, Attila; Walter, Olaf
Abstract : Organometallic actinide compounds have been described in the literature for a long time, for example, reports on the tris‐cyclopentadienide actinide(III) complexes have been around for more than 50 years. Astonishingly however, the solid‐state structures of UCp3 and PuCp3 were still unknown until now. More information can be found in the Communication by O. Walter et al. onpage 2841 .